2023
DOI: 10.1002/pchj.675
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of training effects on English phonological awareness and reading in native Chinese speakers

Abstract: Enhancing English phonological awareness is critical in promoting native English speakers’ reading development. However, less attention has been paid to the role of phonological awareness development for English language learners in a logographic context. This meta‐analysis aims to evaluate the effectiveness of training native Chinese speakers’ English phonological awareness and reading across age groups. Thirty‐three articles, including 37 independent samples, were identified as training studies that reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…This study revealed strong correlations between PA measures and both word reading and reading comprehension skills. Moreover, Jiang et al (2023b) conducted a meta-analysis to examine the effectiveness of PA training among NC speakers. They reported that PA training significantly improved upper elementary students’ word reading abilities.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed strong correlations between PA measures and both word reading and reading comprehension skills. Moreover, Jiang et al (2023b) conducted a meta-analysis to examine the effectiveness of PA training among NC speakers. They reported that PA training significantly improved upper elementary students’ word reading abilities.…”
Section: Introductionmentioning
confidence: 99%